Chinese adolescents’ socioeconomic status and English achievement: the mediating role of parental emotional support - Shasha Xu; Ying Jin (Humanities & Social Sciences Communications)
Abstract Family socioeconomic status (SES) is one of the key indicators of academic achievement, including language achievement. Further investigation of SES’s mechanisms of influence and potential mediators is essential due to the concern regarding the disparities caused by SES in language achievement. This study examines the relation between SES and Chinese adolescents’ English achievement, emphasizing the role of parenting as a conduit for socioeconomic impacts on children and adolescents. The mechanism through which SES influences English achievement was examined in a sample of 1634 junior secondary school students in an urban city in mainland China. A unified model with solid fit indices, comprising both SES and parenting components, was identified through structural equation modeling. As expected, socio-economic disparities appeared to be largely associated with students’ English achievement, and this connection was partially mediated by parental emotional support. Parental emotional support, however, had varied mediating effects that affected the developmental course and shaped achievement outcomes across different SES groups. This study offers valuable insights into the joint contribution of distal SES factors and proximal interactions to achievement outcomes. Intervention efforts and future research implications are discussed.